Antimicrobial Susceptibilities and Plasmid Contents of Neisseria gonorrhoeae Isolates from Commercial Sex Workers in Dhaka, Bangladesh: Emergence of High-Level Resistance to Ciprofloxacin - Bhuiyan, Bahar Uddin (American Society for Microbiology, 1999)
Commercial sex workers (CSWs) serve as the most important reservoir of sexually transmitted diseases (STD), including gonorrhea. Periodic monitoring of the antimicrobial susceptibility profile of Neisseria gonorrhoeae in a high-risk population provides essential clues regarding the rapidly changing pattern of antimicrobial susceptibilities. A study concerning the prevalence of gonococcal infection among CSWs was conducted in Bangladesh. The isolates were examined with regards to their antimicrobial susceptibility to, and the MICs of, penicillin, tetracycline, ciprofloxacin, cefuroxime, ceftriaxone, and spectinomycin by disk diffusion and agar dilution methods. The total plasmid profile of the isolates was also analyzed. Of the 224 CSWs, 94 (42%) were culture positive for N. gonorrhoeae. There was a good correlation between the results of the disk diffusion and agar dilution methods. Some 66% of the isolates were resistant to penicillin, and 34% were moderately susceptible to penicillin. Among the resistant isolates, 23.4% were penicillinase-producing N. gonorrhoeae (PPNG). 60.6% of the isolates were resistant and 38.3% were moderately susceptible to tetracycline, 17.5% were tetracycline-resistant N. gonorrhoeae, 11.7% were resistant and 26.6% had reduced susceptibility to ciprofloxacin, 2.1% were resistant and 11.7% had reduced susceptibility to cefuroxime, and 1% were resistant to ceftriaxone. All PPNG isolates contained a 3.2-MDa African type of plasmid, and a 24.2-MDa conjugative plasmid was present in 34.1% of the isolates. Since quinolones such as ciprofloxacin are recommended as the first line of therapy for gonorrhea, the emergence of significant resistance to ciprofloxacin will limit the usefulness of this drug for treatment of gonorrhea in Bangladesh.